An Accidental Oil Spill Along the Belgian Coast: Results from a CV Study - Karl van Biervliet; Dirk Le Roy; Paulo A.L.D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper offers an economic assessment of the loss of non-use values resulting from different oil spill scenarios along the Belgian Coast. Estimation results show that if no oil spill prevention policy action is undertaken, a significant welfare loss may result. As a matter of fact, contingent valuation estimation results show such a welfare loss ranges from 120 million Euro to 606 million Euro, depending on the size and the frequency of the oil spill under consideration. Therefore, any investment program targeted at the prevention of oil spills, and its damage on the marine environment, can be clearly defended from a cost-benefit perspective as long as its cost is no higher than 120 million Euro.
Keywords: Q51; Q53; Q54; Q58; 330; Oil Spill; Prevention Scenario; Contingent Valuation; Cost Benefit Analysis; Umweltbelastung; Meeresverschmutzung; Willingness to pay; Kosten-Nutzen-Analyse; Küstenregion; Belgien